2015
DOI: 10.1002/ejoc.201403524
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3‐Arylisocoumarins by Using Acyl Anion Chemistry and Synthesis of Thunberginol A and Cajanolactone A

Abstract: A new strategy for the synthesis of 3-arylisocoumarins and 8-hydroxy-3-arylisocoumarins was investigated by using acyl anion chemistry for the initial C-C bond formation. The obtained keto esters and keto lactones as intermediates under-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…Then, reductive elimination from intermediate IV gives the α-arylated ketone and regenerates the Pd 0 L n catalyst. As we have demonstrated (Scheme c) and in agreement with literature, compound 5 yields isocoumarin 3a and methanol as coproduct.…”
supporting
confidence: 92%
“…Then, reductive elimination from intermediate IV gives the α-arylated ketone and regenerates the Pd 0 L n catalyst. As we have demonstrated (Scheme c) and in agreement with literature, compound 5 yields isocoumarin 3a and methanol as coproduct.…”
supporting
confidence: 92%
“…The new method reported by us for the synthesis of 3-arylsubstituted isocoumarins, [7] wherein α-aryl aminonitriles 10 were conveniently used as acyl anion equivalents for the requisite C-C bond formation, has a drawback for the synthesis of 8 and 9, because alkylated α-alkyl aminonitriles 11a require strongly acidic conditions in most cases [8a-8f ] in contrast to alkylated α-aryl aminonitriles 10a for release of the carbonyl functionality ( Figure 2). For sugar-based α-aminonitriles 12, if available and used, the situation with alkylated glycosyl aminonitriles 12a would be even more detrimental given the sensitive functionalities and protections present on the glycosyl part.…”
Section: Resultsmentioning
confidence: 99%
“…Transition-metal-catalyzed C–H activation and alkyne annulation directed by a carboxylate group has been developed for the synthesis of 3,4-disubstituted isocoumarins . Recently, Aidhen et al reported the synthesis of 8-hydroxy-3-arylisocoumarins using acyl anion chemistry . However, the majority of these methods suffer from formation of isomeric mixtures of products and limited substrate scope.…”
mentioning
confidence: 99%
“…7 Recently, Aidhen et al reported the synthesis of 8-hydroxy-3-arylisocoumarins using acyl anion chemistry. 8 However, the majority of these methods suffer from formation of isomeric mixtures of products and limited substrate scope. Thus, a simple, efficient, mild, scalable, regioselective preparation of 8-hydroxy-3-substitued isocoumarins is still highly desirable.…”
mentioning
confidence: 99%